MCQs in general medicine for dental students a system-based approach with dental management considerations - Prabhu, S. R. (Jaypee Brothers Medical Publishers, 2014)
This book includes 900 multiple choice questions (MCQs) and answers and provides a practical way of testing student's knowledge and recall of information